Autophagy and Alzheimer’s Disease: Mechanisms and Impact Beyond the Brain - Zaw Myo Hein; Thirupathirao Vishnumukkala; Barani Karikalan; Aisyah Alkatiri; Farida Hussan; Saravanan Jagadeesan; Mohd Amir Kamaruzzaman; Muhammad Danial Che Ramli; Che Mohd Nasril Che Mohd Nassir; Prarthana Kalerammana Gopalakrishna (Cells, 2025)
Alzheimer’s disease (AD) is a progressive neurodegenerative disorder marked by neuronal loss, cognitive decline, and pathological hallmarks such as amyloid-beta (Aβ) plaques and tau neurofibrillary tangles. Recent evidence highlights autophagy as a pivotal mechanism in cellular homeostasis, mediating the clearance of misfolded proteins and damaged organelles. However, impaired autophagy contributes significantly to AD pathogenesis by disrupting proteostasis, exacerbating neuroinflammation, and promoting synaptic dysfunction. This review aims to scrutinize the intricate relationship between autophagy dysfunction and AD progression, explaining key pathways including macroautophagy, chaperone-mediated autophagy (CMA), and selective autophagy processes such as mitophagy and aggrephagy. This further extends the discussion beyond the central nervous system, evaluating the role of hepatic autophagy in Aβ clearance and systemic metabolic regulation. An understanding of autophagy’s involvement in AD pathology via various mechanisms could give rise to a novel therapeutic strategy targeting autophagic modulation to mitigate disease progression in the future.